THE GROUP OF WORDS INDICATING RANK AND TITLE IN PIRIMQUL QODIROV'S WORKS "YULDUZLI TUNLAR" AND "AVLODLAR DAVONI" - Rakhimov, Abdukarim (Журнал иностранных языков и лингвистики, 2024)
This article explores the group of words indicating rank and title in Pirimqul Qodirov's literary works "Yulduzli Tunlar" and "Avlodlar Davoni". The study examines how Qodirov uses various terms related to state governance, military ranks, and noble titles, shedding light on their semantic functions and cultural significance within the context of his novels. By analyzing the lexicon of these works, the article highlights the role of these titles and ranks in reflecting the social and political hierarchy, as well as the historical and cultural dynamics of the time. The research identifies and categorizes these lexical units, providing insights into the language of power and authority in Uzbek literature. The analysis of these terms enriches our understanding of the socio-political landscape depicted in the novels, offering a deeper appreciation of Qodirov's contribution to Uzbek literary traditions.